Heavy ion beam probing – a tool to study geodesic acoustic modes and alfven eigenmodes in the T-10 tokamak and TJ-II stellarator - Melnikov, A.V.; Krupnik, L.I.; Barcala, J.M.; Bravo, A.; Chmyga, A.A.; Deshko, G.N.; Drabinskij, M.A.; Eliseev, L.G.; Hidalgo, C.; Khabanov, P.O.; Kharchev, N.K.; Komarov, A.D.; et al. (Вопросы атомной науки и техники, 2017)
Heavy ion beam probing (HIBP) is a unique diagnostic for core plasma potential. It operates in the T-10 tokamak and TJ-II flexible heliac. Multi-slits energy analyzers provide simultaneously the data on plasma potential φ (by beam extra energy), plasma density (by beam current) and Bpol (by beam toroidal shift) in 5 poloidally shifted sample volumes. Thus, the poloidal electric field and the electrostatic turbulent particle flux are derived. The fine focused (<1 cm) and intense (100 μA) beams provide the measurements in the wide density interval ne=(0.3...5)×10¹⁹ m⁻³, while the advanced control system for primary and secondary beams provides the measurements in the wide range of the plasma currents in T-10 and magnetic configurations in TJ-II, including Ohmic, ECR and NBI heated plasmas. Low-noise high-gain (10⁷ V/A) preamplifiers with 300 kHz bandwidth and 2 MHz sampling allow us to study quasi-coherent modes like Geodesic Acoustic Modes (GAMs) and Alfvén Eigenmodes (AEs). The spatial location, poloidal rotation velocity and mode numbers for GAMs and AEs were studied in the core plasmas.